Root endophyte induced plant thermotolerance by constitutive chromatin modification at heat stress memory gene loci. (10th January 2021) - Shekhawat, Kirti; Saad, Maged M; Sheikh, Arsheed; Mariappan, Kiruthiga; Al‐Mahmoudi, Henda; Abdulhakim, Fatimah; Eida, Abdul Aziz; Jalal, Rewaa; Masmoudi, Khaled; Hirt, Heribert
Abstract: Global warming has become a critical challenge to food security, causing severe yield losses of major crops worldwide. Conventional and transgenic breeding strategies to enhance plant thermotolerance are laborious and expensive. Therefore, the use of beneficial microbes could be an alternative approach. Here, we report that the root endophyte Enterobacter sp. SA187 induces thermotolerance in wheat in the laboratory as well as in open‐field agriculture. To unravel the molecular mechanisms, we used Arabidopsis thaliana as model plant. SA187 reprogramed the Arabidopsis transcriptome via HSFA2 ‐dependent enhancement of H3K4me3 levels at heat stress memory gene loci. Unlike thermopriming, SA187‐induced thermotolerance is mediated by ethylene signaling via the transcription factor EIN3 . In contrast to the transient chromatin modification by thermopriming, SA187 induces constitutive H3K4me3 modification of heat stress memory genes, generating robust thermotolerance in plants. Importantly, microbial community composition of wheat plants in open‐field agriculture is not influenced by SA187, indicating that beneficial microbes can be a powerful tool to enhance thermotolerance of crops in a sustainable manner. SYNOPSIS: Root endophyte Enterobacter sp. SA187 induces thermotolerance in wheat and Arabidopsis via HSFA2‐ and EIN3‐dependent increased H3K4me3 levels at heat stress memory genes. Beneficial microbes might be used to enhance crop thermotolerance in a sustainable manner. Root endophyte Enterobacter sp. SA187 induces thermotolerance in Arabidopsis and wheat in the laboratory as well as in open‐field agriculture. SA187 reprogramed the Arabidopsis transcriptome via HSFA2‐dependent enhancement of H3K4me3 levels at heat stress memory gene loci. Unlike thermopriming, SA187‐induced thermotolerance is mediated by ethylene signaling‐dependent constitutive H3K4me3 modification of heat stress memory genes. Abstract : Root endophyte Enterobacter sp. SA187 induces thermotolerance in wheat and Arabidopsis via HSFA2‐ and EIN3‐dependent increased H3K4me3 levels at heat stress memory genes. Beneficial microbes might be used to enhance crop thermotolerance in a sustainable manner.